Analisis Tingkat Literasi Digital Remaja Fase Akhir Pengguna Fitur Anonymous Chatbot Telegram - Fahma Tsaltsa Nur Afni; Iky Putri Aristhya (INDO PUBLISHING, 2025)
The development of digital technology opens up new spaces for interaction, but also raises challenges in the form of media abuse. One of them is the use of the anonymous chat bot feature on Telegram which is widely used by late-phase teenagers. This feature provides the freedom to interact without identity, but it is also often a loophole for sexual harassment, inappropriate conversation, and identity abuse. The low digital literacy of adolescents, especially in the aspects of security and media ethics, makes them vulnerable to these risks. This study aims to analyze the level of digital literacy of adolescents in the final phase of the use of anonymous chat bots, with a focus on understanding, attitudes, and awareness of digital ethics. To find accurate results, this study will use the social learning theory of Albert Bandura. Social learning theory explains that a person's behavior and knowledge are not only influenced by internal factors such as habits and experiences, but also influenced by external factors such as culture, social, and environment. The research method uses a descriptive qualitative approach with a constructivist paradigm. Data were obtained through in-depth interviews with three informants aged 18–21 who were active users, and reinforced with related literature. The results of the study show that the level of digital literacy of adolescents is still in the primary to secondary category. Some understand the basic functions of the feature and its potential risks, but have not consistently implemented preventive measures. Meanwhile, adolescents with higher digital literacy tend to be more selective and responsible in using anonymous features. In conclusion, the digital literacy of adolescents in the final phase needs to be improved, especially in the aspects of ethics, security, and media responsibility.